(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The alter identicus has dismissed the alter ego in late modernity, with repercussions for the way psychiatrists view the other. After examining the notions of limit and situation for each of these two ways of viewing the other, we will examine their consequences for diagnostic development. We will detail the example of the ADI-R and the ADOS in the diagnosis of autism spectrum disorders (ASD). We will question the usefulness of defining very broad markers of belonging (alter identicus) that seem to miss their target : to understand a neuroconstructivist development process in which the patient’s creativity (alter ego) contributes significantly to the development of a divergent trajectory.